Evaluating the Validity and Effectiveness of Multiantro Tools in Diverse Applications - Arga, Muhammad Wahyu; Sukamti, Endang Rini; Srianto, Widha; Wahyuti, Sri Ayu; Pamungkas, Okky Indera; Budiarti, Ratna; Nurfadhila, Risti; Prasetyo, Heru (Jorpres (Jurnal Olahraga Prestasi), 2024)
Anthropometry is a science created from a new scientific sub-discipline called physical anthropology which is an implication of the development of anthropological studies. Anthropometry plays a very important role in the world of sports. An ideal anthropometric composition and supported by good technique will produce an athlete's excellent performance in the competition. Anthropometric characteristics, body composition and mass contribute to training and competition performance. Therefore, researchers have developed a multifunctional anthropometric measurement tool, several test items can be carried out simultaneously with the use of this tool, this tool is called 'Multiantro". The tests that can be done simultaneously with this tool are height, weight, sitting height and arm length tests. However, this tool still requires further review, so this study is intended to conduct a concurrent validity test phase of the Multiantro tool so that the results of its measurement can be accounted for. The method used was a cross-sectional design in which data from two instruments, a new instrument and a standardized instrument, were then collected at the same time from the same sample. The new instrument was tested to determine whether the results were consistent with the standardized measurement tool. The analysis results show that there is no significant difference between measurements using the Multiantro tool and measurements using conventional tools that have been standardized before. So it can be concluded that the Multiantro tool is also reliable in anthropometric measurements, just as when using previously existing tools. Even with this tool, tests can be carried out more practically because one tool is used to carry out four different types of test items.